Real and Potential Nursing Problems of Obese Patients With COVID-19 Disease - Pranckūnaitė, Greta; Gerikienė, Vitalija (Slauga. Mokslas ir praktika, 2022)
Problem. Obesity is associated with increased hospitalization, intensive care and risk of death in COVID-19 patients. Therefore, in order to ensure the best possible care for obese patients with coronavirus infection, it is necessary to identify real and potential problems in the care of obese patients with COVID-19 disease. Aim. To analyze the real and potential problems of obese patients with COVID-19 disease. Methods. A qualitative study was carried out using semi-structured interviews and data analysis using the qualitative content analysis method. The study participants were nurses working in the COVID-19 resuscitation unit. Results and Conclusions. According to the statements of the nurses involved in the study, the following real nursing problems in obese patients with COVID-19 disease were identified: fever, respiratory failure, shortness of breath, cough, violations of skin integrity, increased sweating, lack of self-care, limited independent movement and dependence on staff, uncomfortable positioning on the belly, nutritional insufficiency, taste disturbance. The study revealed the following potential nursing problems in obese patients with COVID-19 disease: death, sudden deterioration, fainting, panic attack, bedsores, infection, skin integrity violation, increased sweating, body wasting, obstipation, malnourished, choking and dehydration.